1968
DOI: 10.1042/bj1060783
|View full text |Cite
|
Sign up to set email alerts
|

The metabolism of 3,5-di-tert.-butyl-4-hydroxytoluene in the rat and in man

Abstract: 1. The major metabolites of 3,5-di-tert.-butyl-4-hydroxytoluene (BHT) in the rat are 3,5-di-tert.-butyl-4-hydroxybenzoic acid (BHT-acid), both free (9% of the dose) and as a glucuronide (15%), and S-(3,5-di-tert.-butyl-4-hydroxybenzyl)-N-acetylcysteine. 2. The mercapturic acid does not appear to derive from the usually accepted enzyme mechanism, and may involve a non-enzymic reaction between BHT free radical and cysteine. 3. The ester glucuronide and mercapturic acid found in rat urine are also the major metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

1968
1968
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…Methyl groups at the 1 and 3 positions are sandwiched between two nitro groups. As for the tert-butyl group, there are some reports on the metabolism of tert-butyl groups of butylated hydroxyanisole (BHA) (Astill et al 1960(Astill et al , 1962Akagi et al 1962;Aoki 1962;Daniel et al 1968). Hydroxylation at the tert-butyl group of BHA was not detectable in the rat, dog (Astill et al 1960(Astill et al , 1962 and rabbit (Dacre et al 1956).…”
Section: Discussionmentioning
confidence: 99%
“…Methyl groups at the 1 and 3 positions are sandwiched between two nitro groups. As for the tert-butyl group, there are some reports on the metabolism of tert-butyl groups of butylated hydroxyanisole (BHA) (Astill et al 1960(Astill et al , 1962Akagi et al 1962;Aoki 1962;Daniel et al 1968). Hydroxylation at the tert-butyl group of BHA was not detectable in the rat, dog (Astill et al 1960(Astill et al , 1962 and rabbit (Dacre et al 1956).…”
Section: Discussionmentioning
confidence: 99%
“…These compounds are also metabolites of methyl methanesulfonate (Barnsley, 1968). E. 3,5-DI-TERT-BUTYL-4-HYDROXYTOLUENE Using spectral and chromatographic techniques, Daniel et al (1968) showed that a major metabolite of the food antioxidant 3,5-di-tert-butyl-4-hydroxytoluene (BHT) in the rat was the mercapturic acid (51). Only a trace of this metabolite was present in human urine.…”
Section: ) Alkyl Methanesulfonatesmentioning
confidence: 99%
“…A similar picture is shown by griseofulvin which is extensively excreted in the bile as a conjugate of 4-demethylgriseofulvin (54). A major biliary metabolite of butylated hydroxytoluene (3,5-di-tert-butyl-4-hydroxytoluene) in the rat is the ester glucuronide of 3,5-di-tertbutyl-4-hydroxybenzoic acid which is believed to be partly responsible for the enterohepatic circulation seen in this species (55). However, the free acid is the main fecal metabolite and it seems likely that intestinal hydrolysis occurs prior to its absorption.…”
Section: Reactionsmentioning
confidence: 99%